Does faecal matter reflect location? An initial assessment of isotopic variability between consumed prey remains and faecal matter for wild jaguars*. Issue 5 (3rd September 2019) - Crowley, Brooke E.; Wultsch, Claudia; Kelly, Marcella J.
ABSTRACT: Faecal isotopic analysis may complement other non-invasive wildlife survey tools for monitoring landscape use by carnivores, such as motion-detecting cameras and non-invasive genetic sampling. We analysed carbon, nitrogen, and strontium isotopes in faecal matter produced by jaguars ( Panthera onca ) as well as bones from consumed prey at the Mountain Pine Ridge Forest Reserve (MPR) in Belize, Central America. The MPR is ideally suited for a spatial isotope study as vegetation and geology both vary considerably. The isotopic composition of faecal matter should reflect the habitat and geology where consumed prey lived. We used bone from consumed prey recovered from jaguar scats as a proxy for diet. Faecal matter and bone showed comparable spatial isotopic trends, suggesting that the isotopic composition of jaguar faeces can be used to detect foraging in different habitats (pine forest versus broadleaf forest) or on different geologies (Mesozoic carbonates; Palaeozoic granite, contact metamorphics, and metasediments). This result is reassuring as bones are not always present in carnivore scats. Studying landscape use by cryptic and wide-ranging carnivore species like jaguars remains challenging. Isotopic analysis of faecal matter complements the existing array of non-invasive spatial monitoring tools.